Rekonstruksi konsep ‘Aul’ dalam distribusi waris islam: analisis keadilan dan relevansinya di era modern - nazar, achmad nazarullah (Maliki Interdisciplinary Journal, 2026)
The concept of ‘aul’ in Islamic inheritance law is a mechanism applied when the total shares of heirs exceed the available estate, requiring proportional reduction. Rooted in classical Islamic jurisprudence, ‘aul’ aims to maintain mathematical balance in allocating rights among heirs. However, contemporary social developments and changes in family structures raise questions about its relevance and substantive justice in modern contexts. This study aims to reconstruct the concept of ‘aul’ through a normative juridical analysis by examining classical fiqh literature, the principles of maqāṣid al-sharī‘ah, and the demands of distributive justice today. The findings indicate that although ‘aul’ remains technically applicable, it requires reinterpretation to align with modern notions of fairness. The proposed reconstruction emphasizes a maqāṣid-based proportional approach and legal responsiveness to evolving social realities. This study affirms that ‘aul’ should be understood not merely as a technical mechanism in farā’iḍ, but as a justice-oriented instrument that must adapt to contemporary contexts.